Access and fees in public health care services for the poor: Bangladesh as a case study. (3rd July 2022) - Abdallah, Wahid; Chowdhury, Shyamal; Iqbal, Kazi
ABSTRACT: The redistributive objective of public services critically hinges on the extent to which the poor can avail themselves of such services. We investigate two factors that can compromise redistribution: unequal access and illegal fees. Using a nationally representative survey (a data source less prone to reporting bias), we find that poor patients in Bangladesh are 8–10% less likely to consult public health care services than non-poor patients. Moreover, a large number of patients visiting public health facilities pay 'consultation fees' which are higher than the official rates, indicative of underlying corruption. Taken together, we find that the poor not only visit public health care facilities less frequently, they also pay a larger share of their non-food expenditure as bribes when they do access these facilities. Our results offer important insights into how the redistributive goal of public health care services can be hampered by misgovernance and corruption.